VBA-BASED WAVE VISUALIZATION DESIGN USING MICROSOFT EXCEL AS THE MEDIA FOR LEARNING PHYSICS IN SENIOR HIGH SCHOOL - Ewis Amalya; M. Rahmad; Syahril Syahril (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
This research aimed to design wave visualization based VBA on microsoft excel as a valid physics learning media for senior high school students of class XI. This research used Research and Development method with ADDIE type. The steps of the design of learning media of this wave visualization include Analysis, Design, Development, Implementation, and Evaluation. However, in this research the researchers only implement up to the development step, then conducted media validation using assessment instruments. The instrument used is validation sheets of the wave visualization learning media. assessment is done on three aspects, namely design aspect, learning content aspect, and pedagogic aspect assessed by validator. Validator consists of team experts and users. Expert validator is a lecturer of Physics Education University of Riau, while the user is a teachers from senior high school on pekanbaru. The validation score obtained for the design aspect of the experts and users is 3.62. The validation score on aspects of learning content from the experts and users is 3.60 and the validation score obtained on the pedagogic aspect of the experts and users is 3.73. The validation results of wave visualization based VBA on excel is in the category very high for all aspects assessed, thus this media can be valid and feasible to be used as a valid physics learning media of students class XI in senior high school.